2017
DOI: 10.1093/rheumatology/kex254
|View full text |Cite
|
Sign up to set email alerts
|

Comparing biosimilar SB2 with reference infliximab after 54 weeks of a double-blind trial: clinical, structural and safety results

Abstract: ObjectivesSB2 is a biosimilar to the reference infliximab (INF). Similar efficacy, safety and immunogenicity between SB2 and INF up to 30 weeks were previously reported. This report investigates such clinical similarity up to 54 weeks, including structural joint damage.MethodsIn this phase III, double-blind, parallel-group, multicentre study, patients with moderate to severe RA despite MTX were randomized (1:1) to receive 3 mg/kg of either SB2 or INF at 0, 2, 6 and every 8 weeks thereafter. Dose escalation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 30 publications
1
55
0
1
Order By: Relevance
“…Biosimilars are reproductions of their originator counterparts, are usually less expensive and therefore provide a potential opportunity to improve patient access. An increasing number of biosimilars are coming into clinical use [3], and so far, no clinical studies have shown any unexpected effects of starting patients on a biosimilar instead of an originator drug [4][5][6][7][8]. However, to achieve a significant impact on health budgets, it is not sufficient that only new patients starting biologic therapy are prescribed biosimilars.…”
Section: Introductionmentioning
confidence: 99%
“…Biosimilars are reproductions of their originator counterparts, are usually less expensive and therefore provide a potential opportunity to improve patient access. An increasing number of biosimilars are coming into clinical use [3], and so far, no clinical studies have shown any unexpected effects of starting patients on a biosimilar instead of an originator drug [4][5][6][7][8]. However, to achieve a significant impact on health budgets, it is not sufficient that only new patients starting biologic therapy are prescribed biosimilars.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1252 studies were identified through electronic searches, and 13 studies were selected for a full‐text review based on the title and abstract details (). However, six of the 13 studies were excluded, because of duplication ( n = 2), MTX‐naïve patients ( n = 2), no data on ACR response data ( n = 1) and short follow‐up period ( n = 1) (). A study by Abe et al .…”
Section: Resultsmentioning
confidence: 99%
“…was not included, because the study did not provide data on ACR response as the efficacy outcome. Thus, seven RCTs that included 2606 patients (1316 events for efficacy and 262 events for safety) met the inclusion criteria (Table ). All the RCTs provided data on efficacy and safety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations